Michel Foucault: Sujeto e historia - Castro, Edgardo (ARFIL y UNL, 2018)
This article describes the evolution of the theme of the subject in the work of Michel Foucault. More precisely, it develops the relationship between subject andhistory, from his first works, dedicated to the history of psychology and of madness, to his courses devoted to biopolitics.